Écologies, performances, pouvoirs : questionner l’image d’architecture au prisme des études visuelles - Ozdoba, Marie-Madeleine (Opus Incertum, 2025)
As a vehicle for societal and ecological projection, the architectural image – understood as encompassing both representations of architectural and urban projects and the broader category of images produced within, for, and by architectural communication – constitutes a uniquely operative corpus within the framework of globalized visual culture. How, then, can its underrepresentation within the diverse materials considered by the interdisciplinary field of visual studies be explained? Drawing on examples from Francophone, Germanophone, and Anglophone scholarly traditions, this article traces the missed encounter between two largely incompatible conceptions of the architectural image – differing in terms of object, methodology, and epistemological stakes – characteristic of visual studies on the one hand and architectural and urban research on the other. It then outlines the conditions under which such an encounter might become possible, mobilizing the concepts of ‘ecology’, ‘performativity’, and ‘power’ of images as critical tools for reexamining representations of/for architecture. Crucially, integrating the architectural image into the agenda of visual studies necessitates a crosspollination between image theory and architectural history.